2020
DOI: 10.1177/8756479320963041
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Umbilical Cord Diameter as an Indicator of Fetal Growth and Perinatal Outcome

Abstract: Objective: To determine whether the assessment of umbilical cord diameter (UCD) is a viable indicator of fetal growth and perinatal outcome. Material and Methods: A total of 652 singleton pregnancies between 10 and 40 weeks of gestation were reviewed for this study. The UCD was measured vertically in the longitudinal section, adjacent to its insertion at the fetal abdomen. Other fetal biometrics were measured according to standard measurement protocols. The perinatal outcome of each patient case was also recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…were highly statistically significant positive correlation between gestational age an Umbilical cord diameter (p<0.001), BPD (p<0.001), FL (p<0.001), AC (p<0.001), AFI (p<0.001) and estimated fetal Udoh et al [6] supported Our results which UCD increased with widely used sonographic measurements used to provide and estimation of GA and FW (such as BPD, HC, FL, and AC). Afroze et al [7] Reported a tight relationship between widely used fetal metrics for GA and UCD.…”
Section: Resultssupporting
confidence: 85%
“…were highly statistically significant positive correlation between gestational age an Umbilical cord diameter (p<0.001), BPD (p<0.001), FL (p<0.001), AC (p<0.001), AFI (p<0.001) and estimated fetal Udoh et al [6] supported Our results which UCD increased with widely used sonographic measurements used to provide and estimation of GA and FW (such as BPD, HC, FL, and AC). Afroze et al [7] Reported a tight relationship between widely used fetal metrics for GA and UCD.…”
Section: Resultssupporting
confidence: 85%
“…A wide diameter of cord indicates a good health of newborn. Udoh et al, Lee et al and Tahmasebi et al also reported similar results in their study (15)(16)(17). The only limitations of these studies were ultrasound guided measurement of cord thickness.…”
Section: Discussionsupporting
confidence: 59%
“…They also showed that there was a poor fetal outcome in 50 pregnant women whose umbilical cord diameter was below the average in the first and second trimesters. [14] Proctor et al investigated the relationship between umbilical cord diameter and fetal weight in 497 pregnant women at 18-41 weeks of gestation. They showed a positive correlation of umbilical cord diameter with birth weight and placental weight.…”
Section: Discussionmentioning
confidence: 99%